2009
DOI: 10.1016/j.adolescence.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Q‐sort measure of identity processing style: The identity processing style Q‐sort☆

Abstract: Identity styles represent strategies individuals use to explore identity‐related issues. Berzonsky (Berzonsky, M. D. (1992). Identity style and coping strategies. Journal of Personality, 60, 771–788) identified three styles: informational, normative, and diffuse. In three studies, this paper presents (a) the identity processing style Q‐sort (IPSQ), a new measurement technique for assessing identity styles, along with the reliability and validity of three criterion sorts that represent “ideal types” for the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…The IPSQ has a test-retest reliability of .71 (Pittman et al 2009). Past studies, which used the IPSQ, have shown that there is a moderate negative correlation between informational and normative styles (r = -.38 in the American sample (Pittman et al 2009); and -.46 in the Turkish sample (Eryigit and Kerpelman 2009)).…”
Section: Identity Stylesmentioning
confidence: 98%
See 4 more Smart Citations
“…The IPSQ has a test-retest reliability of .71 (Pittman et al 2009). Past studies, which used the IPSQ, have shown that there is a moderate negative correlation between informational and normative styles (r = -.38 in the American sample (Pittman et al 2009); and -.46 in the Turkish sample (Eryigit and Kerpelman 2009)).…”
Section: Identity Stylesmentioning
confidence: 98%
“…However, the ISI has certain limitations such that some items focus on certain identity domains, other items ask domain-free general questions; items are not consistently phrased as ongoing actions; and the instrument does not assess the relative importance of different orientations (see Eryigit and Kerpelman 2009;Pittman et al 2009;Vleioras 2007 for more information on its limitations). In an effort to increase the ability to capture the complexity of individuals' conceptualization of their orientation to identity work, the Identity Processing Styles Q-Sort (IPSQ: Pittman et al 2009) was developed and tested with multiple samples.…”
Section: Identity Stylesmentioning
confidence: 99%
See 3 more Smart Citations